Komparasi Efektivitas Metode Pembelajaran terhadap Pemahaman Konsep Kimia - Indah Juitaningsih, (Jurnal Bintang Pendidikan Indonesia, 2024)
The purpose of this study is to determine the influence of learning methods on the understanding of chemical concepts among high school students in South Jakarta. The method employed is experimentation. The population size in this study is 611 students, thus the sample taken is 10% of the population, which is 60 students. The results of hypothesis testing indicate a significant influence of the learning method on the understanding of chemical concepts among high school students in South Jakarta.